Innovative Training Solutions for Quality Managers. (2015) - Moldovan, Liviu
Abstract: This paper presents the design of a pedagogical methodology for training of quality managers by employment of Activity Based Training (ABT) and Student Response System (SRS). The recent developments and results obtained during pilot testing of the new pedagogical models and services are presented. It is demonstrated the professional training by means of ABT learning environment, employing a generalised quality assurance process in an organization. It makes training experiential allowing for periods of reflection. Trainees' outcomes are evaluated with SRS that are an integrated component of the course. The research results and practical issues deduced from the implementation phase demonstrate the quality of feedback from trainees, the effectiveness of the different discussion methods, some logistical considerations, timed versus non-timed voting sessions, the instructor's role in explaining the alternatives of a quiz and the main problems that may become drawbacks of the evaluation system.